Norms and Contracting - Kessler, Judd B.; Leider, Stephen (Management Science, 2012)
We argue that contracts establish the norms of a relationship and that individuals incur disutility when deviating from these norms. In a laboratory experiment, we allow agents to make simple contracts before they play one of four games, and the most effective contract always includes an unenforceable “handshake” agreement to take the first-best action. In three games, a contract with only this handshake agreement is (at least weakly) optimal. The handshake is particularly effective in games with strategic complements. Our results highlight an explanation for contractual incompleteness: establishing a norm can effectively substitute for weak enforceable restrictions. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.